LOFAR Observations of Substructure Within a Traveling Ionospheric Disturbance at Mid‐Latitude. Issue 1 (19th January 2023) - Dorrian, Gareth; Fallows, Richard; Wood, Alan; Themens, David R.; Boyde, Ben; Krankowski, Andrzej; Bisi, Mario; Dąbrowski, Bartosz; Vocks, Christian
Abstract: The large scale morphology and finer sub‐structure within a slowly propagating traveling ionospheric disturbance (TID) are studied using wide band trans‐ionospheric radio observations with the LOw Frequency ARray (LOFAR; van Haarlem et al., 2013, https://doi.org/10.1051/0004-6361/201220873 ). The observations were made under geomagnetically quiet conditions, between 0400 and 0800 on 7 January 2019, over the UK. In combination with ionograms and Global Navigation Satellite System Total Electron Content anomaly data we estimate the TID velocity to ∼60 ms −1, in a North‐westerly direction. Clearly defined substructures with oscillation periods of ∼300 s were identified within the TID, corresponding to scale sizes of 20 km. At the geometries and observing wavelengths involved, the Fresnel scale is between 3 and 4 km, hence these substructures contribute significant refractive scattering to the received LOFAR signal. The refractive scattering is strongly coherent across the LOFAR bandwidth used here (25–64 MHz). The size of these structures distinguishes them from previously identified ionospheric scintillation with LOFAR in Fallows et al. (2020), https://doi.org/10.1051/swsc/2020010, where the scale sizes of the plasma structure varied from ∼500 m to 5 km. Plain Language Summary: Radio waves traveling from distant cosmic radio sources undergo distortions as they transit the Earth's ionosphere. The distortions, usually referred to as ionospheric scintillation, permit the remote characterization of ionospheric behavior. In this study we use this phenomena to extract information about the presence of a traveling ionospheric disturbance (TID), including observing substructure within the TID of sizes ∼20 km. The effect is to create sequences of radio signal focusing and enhancement followed by signal fading in observations of this radio scintillation using the LOw Frequency ARray telescope. Key Points: A slow moving traveling ionospheric disturbance was detected exhibiting substantial internal substructure on scales of ∼20 km The propagation of the traveling ionospheric disturbance was estimated by several methods to be ∼65 ms −1 in a North Westerly direction Substructure detected within the traveling ionospheric disturbance was larger than the Fresnel scale for the observation geometries and generated refractive scattering